An intervention of four weeks of time-restricted eating (16/8) in male long-distance runners does not affect cardiometabolic risk factors - Richardson, C. E.; Tovar, A. P.; Davis, B. A.; Van Loan, M. D.; Keim, N. L.; Casazza, G. A. (Nutrients, 2023)
Timing of nutrient intake for athletes may affect exercise performance and cardiometabolic factors. Our objective was to examine the effect of time-restricted eating (TRE) on cardiometabolic health. Using a cross-over study design, 15 endurance-trained male runners were randomized to either a normal dietary pattern (ND) first (12 h eating/fasting times) followed by time-restricted eating (TRE) pattern (16 h fast; 8 h eating) or the reverse, with a 4-week washout period between interventions. Body composition, resting energy expenditure, blood pressure and serum insulin, glucose and lipids were measured using standard laboratory methods. Exercise training and dietary intake (calories and macronutrients) were similar across interventions. No significant differences were observed in resting energy expenditure, markers of insulin resistance, serum lipids or blood pressure. Body composition did change significantly (p < 0.05) with whole body fat mass (-0.8 ± 1.3 kg with TRE vs. +0.1 ± 4.3 kg with ND), leg fat mass (-0.3 ± 0.5 kg with TRE vs. +0.1 ± 0.4 kg with ND), and percent body fat (-1.0 ± 1.5% with TRE vs. +0.1 ± 1.3% with ND) declining more in the TRE intervention, with no change in fat-free mass. This study is one of a few to investigate the effects of an isocaloric 16/8 TRE eating pattern in trained endurance athletes and confirms no change in cardiometabolic risk factors. In conclusion, TRE is not detrimental to cardiometabolic health in endurance-trained male runners but could be beneficial on exercise performance by reducing fat mass.